STRATEGI DALAM MENGEMBANGKAN BISNIS UMKM PADA ERA DIGITAL DI PAGUYUBAN GRAND VIONA CISEENG - Purwanti; Akbar, Mada Faisal; Sudarsono, Agus (Abdi Jurnal Publikasi, 2024)
The rapid advancement of technology in Indonesia makes everything easier, one of which is opening up many opportunities for business sector players. MSME business actors (Micro, Small and Medium Enterprises) are starting to open a number of businesses easily nowadays, we can see this with the large number of MSME business actors opening businesses by utilizing online media on social media and a number of applications that support their business. Technological advances that are becoming more sophisticated every day are changing the behavior of our society to become fond of online shopping. Especially during the Covid pandemic yesterday, the amount of online shopping increased drastically because many people were not allowed to leave the house because of the PSBB. However, as many online MSME businesses are being built, many businesses are also going bankrupt because competition between competitors is getting tougher, so every business person must be able to implement appropriate marketing strategies and not be left behind in using technology which is very helpful in the success of an MSME business. the. Even after the pandemic passed, online marketing has become more widespread because of its ease in marketing products or services and on the one hand, it also makes it easier for buyers to shop online. The methods used include lectures used to convey knowledge to members in general regarding the importance of knowledge about digital marketing, demonstrations used to provide skills in using smartphone applications for digital marketing that they will use in starting a business venture and developing it, questions and answers used to complete things. -things that have not been accommodated by the two methods above and evaluation of activity results. There were 35 participants who attended, consisting of administrators and community members, lecturers and students at Pamulang University. The activity was carried out through a question and answer discussion, with resource persons providing counseling and followed by participants gathered in the hall who enthusiastically listened using a laptop connected to the LCD. Thank God, the activity went smoothly, participants were enthusiastic about sharing business experiences and obstacles faced and practicing how to use electronic devices or the internet and combined with various marketing strategies and various digital media platforms which make it easier for consumers or customers to communicate with each other online.